Biomass‐Derived Porous Carbon Prepared from Egg White for High‐performance Supercapacitor Electrode Materials. Issue 24 (26th June 2019) - Zhu, Ying; Fang, Tingting; Hua, Junqiang; Qiu, Shujun; Chu, Hailiang; Zou, Yongjin; Xiang, Cuili; Huang, Pengru; Zhang, Kexiang; Lin, Xiangcheng; Yan, Erhu; Zhang, Huanzhi; et al.
Abstract: Using egg white as raw material, the activated carbon materials with nitrogen doping were synthesized by a two‐step method involving carbonization and activation. Structure characterization showed this porous carbon had a three‐dimensional honeycomb structure composed of interconnected micropores and mesopores, which resulted in a high specific surface area of 2918 m 2  g −1 . Due to KOH activation, the appropriate ratio of micropore to mesopore could optimize the diffusion channel of electrolyte ion and increase the contact area between electrolyte and electrode. Thus the egg white‐derived porous carbon (EWC) showed outstanding electrochemical properties as supercapacitor electrode. In three‐electrode system, a high specific capacitance of 335 F g −1 could be achieved at a current density of 0.5 A g −1, and only 8.3% of capacitance was lost after 10000 cycles. For the symmetrical supercapacitor fabricated with as‐prepared carbon material, it exhibited a specific capacitance of 68 F g −1 and a maximum energy density of 13.6 W h kg −1 . Abstract : Egg white‐derived porous carbon was successfully synthesized through low‐temperature calcination and following activation by KOH, which exhibits high specific surface area (2918 m 2  g −1 ), outstanding electrochemical performance (335 F g −1 at 0.5 A g −1 ) and improved rate performance (240 F g −1 at 20 A g −1 ). In addition, symmetrical supercapacitor fabricated with the as‐prepared carbon material exhibits a high energy density of 13.6 W h kg −1 .